‘Mens sana in corpore Sano’: Home food consumption implications over child cognitive performance in vulnerable contexts - Company-Córdoba, Rosalba; Accerenzi, Michela; Simpson, Ian Craig; Ibáñez-Alfonso, Joaquín A. (Frontiers in Psychology, 2022)
Diet directly affects children's physical and mental development. Nonetheless, how food insecurity and household food consumption impact the cognitive performance of children at risk of social exclusion remains poorly understood. In this regard, children in Guatemala face various hazards, mainly related to the socioeconomic difficulties that thousands of families have in the country. The main objective of this study was to analyze the differences in cognitive performance considering food insecurity and household food consumption in a sample of rural and urban Guatemalan children and adolescents at risk of social exclusion. Child cognitive performance was assessed in 134 children and adolescents (age M = 11.37; SD = 3.54) from rural and urban settings. Language, attention, and executive functions were assessed using neuropsychological tasks. Differences in cognitive performance in each level of food insecurity and household diet consumption were compared by using the Mann-Whitney U test. A stepwise multivariate regression analysis was conducted to determine which factors may influence cognitive scores. The results showed that rural and urban groups did not differ in terms of food insecurity. However, considering just rural areas, differences were found between groups with food security and insecurity in attention and executive function tasks. Moreover, differences were found in food consumption for certain groups of food (e.g., meat, U= 1146, p <.001, g=.72). Regarding regressions, protein food consumption (e.g., meat and fish), which is related to having a more balanced diet, was a relevant factor in executive performance. Contrary to what we expected, performance in attentional tasks was not related to the consumption of any food group. These findings could help politicians and decision-makers to select actions focused on improving diet balance and food security in families at risk of social exclusion. It is necessary to carry out more specific studies on the factors related to diet that affect the cognitive development of minors at risk of social exclusion. In addition, it is necessary to study the implementation of alternative interventions that include low-cost nutrients, thus ensuring that minors have access to a more balanced diet.